2022
DOI: 10.1136/lupus-2022-000840
|View full text |Cite
|
Sign up to set email alerts
|

Infertility in systemic lupus erythematosus: what rheumatologists need to know in a new age of assisted reproductive technology

Abstract: Fertility is often a concern for women with SLE. In addition to known indirect factors that influence the ability of a woman with SLE to become pregnant, such as cytotoxic agents, other medications, advanced age and psychosocial effects of the disease, direct disease-related factors are believed to influence fertility. These include diminished ovarian reserve, menstrual irregularities (a function of disease activity) and the presence of antiphospholipid antibodies. The question of whether SLE intrinsically aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…Autoimmune diseases are a large group of chronic disorders mediated by immune responses to self-antigens, such as rheumatoid arthritis (RA) [19], antiphospholipid syndrome [60], systemic lupus erythematosus [61], multiple sclerosis (MS) [62], autoimmune hypothyroidism [63]. A range of mental and somatic symptoms are present in these disorders, with fatigue being one of the most common and challenging symptoms to manage [64].…”
Section: Fatigue In Autoimmune Diseases Affecting Fertilitymentioning
confidence: 99%
“…Autoimmune diseases are a large group of chronic disorders mediated by immune responses to self-antigens, such as rheumatoid arthritis (RA) [19], antiphospholipid syndrome [60], systemic lupus erythematosus [61], multiple sclerosis (MS) [62], autoimmune hypothyroidism [63]. A range of mental and somatic symptoms are present in these disorders, with fatigue being one of the most common and challenging symptoms to manage [64].…”
Section: Fatigue In Autoimmune Diseases Affecting Fertilitymentioning
confidence: 99%
“…Several studies have found a correlation between SLE and decreased ovarian reserve, independent of cyclophosphamide (CYC) use, but others have not; [47][48][49][50][51][52] a published review devoted to this topic presents more detailed information on individual studies. 53 Several indirect risk touchREVIEWS in RMD factors contribute to infertility and delayed conception in women with SLE, including medication use. 54 Paediatric SLE may be associated with menstrual irregularity and pituitary hormone abnormalities.…”
Section: Concerns About Fertility and Conceptionmentioning
confidence: 99%
“…Системная красная волчанка (СКВ) является хроническим мультисистемным аутоиммунным заболеванием, при котором сама активность заболевания и лекарственные препараты, используемые для его лечения, могут оказывать неблагоприятное воздействие на функцию яичников. Чаще всего системная красная волчанка поражает молодых женщин, таким образом, влияя на фертильность и репродуктивную функцию [2]. Все больше данных свидетельствуют о том, что диагноз СКВ сам по себе может повлиять на способность зачать и выносить здорового ребенка, так как сохраняется высокий риск осложнений беременности, включая повышенный риск мертворождения (отношение рисков 16,49; р<0,001) и внутриутробной гибели плода (отношение рисков 7,55; p<0,0001) [5].…”
unclassified
“…В качестве предикторов данных осложнений рассматриваются высокая активность СКВ, серопозитивность по антиовариальным, антинуклеарным и антифосфолипидным антителам, проводимое антигипертензивное лечение и низкое количество тромбоцитов [6; 7]. К косвенным причинам развития субфертильности и снижения овариального резерва у женщин с СКВ могут быть отнесены старение (естественное уменьшение овариального резерва с возрастом женщины, снижение вероятности зачатия) [8], хирургические операции на яичниках, химио-и лучевая терапия, инфекции органов малого таза, генетические аномалии [9], психосоциальные последствия основного заболевания (низкая самооценка, физические ограничения, снижение либидо, высокий уровень депрессии при СКВ), низкий уровень антиоксидантов и витамина D в сыворотке крови [10], пограничные показатели индекса массы тела, а также использование цитотоксических и других лекарственных препаратов [2].…”
unclassified